Platelet Hyperaggregability in Ischemic Cerebrovascular Disease and Effects of Aspirin - Kusunoki, M; Kimura, K; Nagatsuka, K; Isaka, Y; Uyama, O; Yoneda, S; Abe, H (Thrombosis and Haemostasis, 1982)
Platelet aggregation was studied in 24 patients in the chronic stage of ischemic cerebrovascular disease (CVD), with cerebral affluent and effluent blood, i.e., carotid arterial and internal jugular venous blood, and also with peripheral venous blood. Aggregation tests were performed at various final concentrations of sodium arachidonate (A.A.) and ADP. In 17 patients, not taking aspirin, platelet aggregability in jugular venous blood was significantly accentuated compared with that in arterial and peripheral venous blood. This tendency was more marked in the patients with cerebral artery stenosis and/or occlusion than in those with normal cerebral angiogram. In 7 patients taking 500 mg or more oral aspirin, aggregation differences across the brain were not observed and A.A. aggregation and the second phase of ADP aggregation were completely suppressed. These results suggest that a prophylactic administration of aspirin may be beneficial for patients in chronic stage of CVD.
Keywords: Platelet aggregation; Ischemic cerebrovascular disease; Cerebral affluent and effluent blood; Aspirin